2016
DOI: 10.1093/eurheartj/ehv713
|View full text |Cite
|
Sign up to set email alerts
|

A circular RNA protects the heart from pathological hypertrophy and heart failure by targeting miR-223

Abstract: These findings disclose a novel regulatory pathway that is composed of HRCR, miR-223, and ARC. Modulation of their levels provides an attractive therapeutic target for the treatment of cardiac hypertrophy and heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
608
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 765 publications
(628 citation statements)
references
References 47 publications
9
608
0
2
Order By: Relevance
“…While circ-Foxo3 promotes cardiac cell death, a circular RNA (HRCR) was found to protect the heart from pathological hypertrophy and heart failure by sequestering and inhibiting miR-223 activity as an endogenous miRNA sponge. 23 In general, circRNAs in the cardiovascular system seem promising as therapeutic targets. Cancer Bachmayr-Heyda and colleagues were the first to report a global reduction of circRNA abundance in colorectal cancer cell lines and cancer tissues compared to normal tissues, and they discovered a negative correlation between global circular RNA abundance and proliferation.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…While circ-Foxo3 promotes cardiac cell death, a circular RNA (HRCR) was found to protect the heart from pathological hypertrophy and heart failure by sequestering and inhibiting miR-223 activity as an endogenous miRNA sponge. 23 In general, circRNAs in the cardiovascular system seem promising as therapeutic targets. Cancer Bachmayr-Heyda and colleagues were the first to report a global reduction of circRNA abundance in colorectal cancer cell lines and cancer tissues compared to normal tissues, and they discovered a negative correlation between global circular RNA abundance and proliferation.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Genome-wide RNA-sequencing analyses have now identified a considerable number of circRNAs derived from backsplicing. Although they are generally expressed at low levels, increasing evidence has shown that circRNAs are linked to physiological development 15 and different diseases, such as neurological dystrophy, 21 cardiovascular diseases, [22][23][24][25] and cancer. [26][27][28] Recently, circRNAs have also been shown to be enriched and stable in plasma, 29 saliva, 30 and even in serum exosomes, 31 indicating the potential of circRNAs as readable biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, two more bioinformatically oriented studies profiled circRNAs in human, mouse, and rat heart tissue and provided a comprehensive catalog of RNase R-resistant circRNA species. 4,5 Recently, a heart-related circRNA was proposed to control hypertrophy, 6 suggesting that circRNAs may elicit functions in cardiomyocytes as well.…”
Section: Editorialmentioning
confidence: 99%
“…4,5 Recently, a heart-related circRNA was proposed to control hypertrophy, 6 suggesting that circRNAs may elicit functions in cardiomyocytes as well.…”
mentioning
confidence: 99%
“…In addition, statistically based splicing detection revealed that tissue-specific RNAs in the heart and lung are markedly induced during human fetal development [3]. Recent studies in this field have revealed that circRNAsare involved in several diseases, such as Alzheimer's disease [4], heart failure [9], Moyamoy disease [10], and cancers [5,6,[11][12][13][14], whereby they function as miRNA sponges. Furthermore, researchers have identified more than 400 circRNAs in human cell-free saliva (CFS) [15] and have detected thousands of circRNAs in human blood from healthy individuals [16], suggesting that circRNAs could exist in some body fluids.…”
Section: Introductionmentioning
confidence: 99%